2013
DOI: 10.1371/journal.pone.0071350
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Sequencing and Transcriptome Analysis of Wolfiporia cocos to Reveal Genes Related to Biosynthesis of Triterpenoids

Abstract: Wolfiporia cocos Ryvarden et Gilbertson is a saprophytic fungus in the Basidiomycetes. Its dried sclerotium is widely used as a traditional crude drug in East Asia. Especially in China, the dried sclerotium is regarded as the silver of the Chinese traditional drugs, not only for its white color, but also its medicinal value. Furthermore, triterpenoids from W. cocos are the main active compounds with antitumor and anti-inflammatory activity. Biosynthesis of the triterpenoids has rarely been researched. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 15 publications
2
54
1
Order By: Relevance
“…24 Likewise, transcriptome analysis of the medicinally relevant Wolfiporia cocos identified several P450s that were upregulated simultaneously with its OSC. 205 Contrastingly, the genome of A. fumigatus shows that it contains multiple genes encoding OSC as opposed to a single copy. Furthermore, the putative enzymes related to helvolic acid 115 production are located in a gene cluster encoding protostadienol 118 synthase, multiple P450s, a reductase, acyltransferases and a dehydrogenase.…”
Section: Fungal Triterpenoidsmentioning
confidence: 99%
“…24 Likewise, transcriptome analysis of the medicinally relevant Wolfiporia cocos identified several P450s that were upregulated simultaneously with its OSC. 205 Contrastingly, the genome of A. fumigatus shows that it contains multiple genes encoding OSC as opposed to a single copy. Furthermore, the putative enzymes related to helvolic acid 115 production are located in a gene cluster encoding protostadienol 118 synthase, multiple P450s, a reductase, acyltransferases and a dehydrogenase.…”
Section: Fungal Triterpenoidsmentioning
confidence: 99%
“…Two genes, oxidosqualene synthase and squalene epoxidase, were identified in the antitumor clavaric acid producer Hypholoma sublaterium (a basidiomycete), and are expected to be required for the production of this secondary metabolite [225,226]. In an effort to elucidate the biosynthesis of lanosterane-type triterpenoids in Wolfiporia and Ganoderma, genomic and transcriptomic studies were published by several groups [227][228][229][230]. These studies suggested that Ganoderma has two oxidosqualene-lanosterol cyclases, with one homolog dedicated to either ergosterol or triterpenoid natural product biosynthesis.…”
Section: Fungal Triterpenoid Biosynthesismentioning
confidence: 99%
“…Total RNA extraction was conducted from mycelium and primordia samples by using TRIzol reagent (Invitrogen, USA) followed by the integrity evaluation using Agilent Technology 2100 Bioanalyzer (Agilent Technologies, USA). Two cDNA libraries were generated as previous reported and paired‐end sequenced by Illumina Hiseq 2000 platform (Illumina, USA) at Beijing Genomics Institute (BGI) (Shenzhen, China). The raw data has been deposited in the National Center for Biotechnology Information (NCBI) Sequence Read Archive (SRA) under accession number SRP100485 and associated with Bioproject PRJNA369728.…”
Section: Methodsmentioning
confidence: 99%